Assessment of refinement of template‐based models in CASP11. (15th June 2016) - Modi, Vivek; Dunbrack, Roland L.
ABSTRACT: CASP11 (the 11th Meeting on the Critical Assessment of Protein Structure Prediction) ran a blind experiment in the refinement of protein structure predictions, the fourth such experiment since CASP8. As with the previous experiments, the predictors were provided with one starting structure from the server models of each of a selected set of template‐based modeling targets and asked to refine the coordinates of the starting structure toward native. We assessed the refined structures with the Z‐scores of the standard CASP measures, which compare the model‐target similarities of the models from all the predictors. Furthermore, we assessed the refined structures with "relative measures, " which compare the improvement in accuracy of each model with respect to the starting structure. The latter provides an assessment of the extent to which each predictor group is able to improve the starting structures toward native. We utilized heat maps to display improvements in the Calpha–Calpha distance matrix for each model. The heat maps labeled with each element of secondary structure helped us to identify regions of refinement toward native in each model. Most positively scoring models show modest improvements in multiple regions of the structure, while in some models we were able to identify significant repositioning of N/C‐terminal segments and internal elements of secondary structure. The best groups were able to improve more than 70% of the targets from the starting models, and by an average of 3–5% in the standard CASP measures. Proteins 2016; 84(Suppl 1):260–281. © 2016 Wiley Periodicals, Inc.